Republic of Moldova : Ad Hoc Review Under the Extended Credit Facility; Request for Augmentation and Rephasing of Access, Modification of Performance Criteria, and Completion of the Inflation Consultation Under the Extended Credit Facility and Extended Fund Facility Arrangements-Press Release; Staff Report; and Statement by the Executive Director for the Republic of Moldova. (IMF Staff Country Reports; Country Report ;, 2022)
The economy rebounded strongly from the pandemic recession last year while prudent macroeconomic management maintained robust buffers. But the war in Ukraine and the international sanctions imposed on Russia and Belarus have resulted in significant spillovers to Moldova, with implications yet to fully play out. At the outbreak of hostilities, FX market pressures triggered significant foreign currency interventions and bank deposit withdrawals, while dollarization has intensified. Moldova has received the highest per capita inflow of Ukrainian refugees (17 percent of the total population), of which about 100,000 refugees (4 percent of the total population) remain in Moldova. Driven by rising food and energy prices, inflation accelerated further above the target band.